Re-animating the mathematical concept: A materialist look at students practicing mathematics with digital technology - Chorney, Sean (Frontline Learning Research, 2017)
This paper proposes a philosophical approach to the mathematical engagement involving students and a digital tool. This philosophical proposal aligns with other theories of learning that have been implemented in mathematics education but rearticulates some metaphors so as to promote insight and ideas to further support continued investigations into the learning of mathematics. In particular, this philosophical proposal takes seriously the notion that a priori to activity, there are no objects which in turn challenge the notions of intention, affordance and/or representation. To exemplify this perspective, two episodes of grade nine students using a dynamic geometry software are analysed to elaborate how mathematics can be seen to emerge from working with a tool.